Weighted signal-to-noise ratio average routing metric for dynamic sequence distance vector routing protocol in mobile ad-hoc networks - Elshaikh, M; Mohd Fairuz, Muhamad Fadzil; Kamel, Nidal S.; Che Muhammad Nor, Che Isa (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/